Haydn - Landon, H. C. Robbins (Howard Chandler Robbins); Raynor, Henry (London : Faber and Faber Ltd, 1972)
A biography of the eighteenth-century Austrian composer responsible for the creation of the modern orchestra and numerous advances in musical techniques
A biography of the eighteenth-century Austrian composer responsible for the creation of the modern orchestra and numerous advances in musical techniques.
Keywords: Haydn, Joseph, -- 1732-1809.; Composers